The Aesthetics of Nature and the Cinematic Sublime: A Creative Investigation into an Organic Transcendental Film Style - Jennings, Danny Roy (Curtin University, 2017)
The aim of this practice-based screen arts doctoral thesis is to investigate how cinematic representations of nature evoke an aesthetic of the sublime. The thesis answers this research question both through experimental film practice and critical analysis of theoretical and artistic texts. Informed by concepts such as the sublime, transcendence, the metaphysical imagination, critical realism and phenomenology, and the films Werner Herzog and Andrei Tarkovsky, this thesis investigates an organic transcendental film style.